Limonoids from the fruits of Chisocheton erythrocarpus and their mosquito larvicidal activities - Ngadni, Muhammad Afiq; Chong, Soon-Lim; Hazni, Hazrina; Asib, Norhayu; Ishak, Intan Haslina; Mohmad Misnan, Norazlan; Supratman, Unang; Awang, Khalijah (Elsevier, 2024)
Phytochemical study of the fruits of Chisocheton erythrocarpus (Hiern) allowed the identification of eight undescribed limonoids, namely erythrocarpines O – V (1–6, 7a and 7b), along with seven known compounds. The structures of these compounds were elucidated based on spectroscopic and HRMS data, along with electronic circular dichroism to configure the absolute configuration. Erythrocarpines O and P are γ-hydroxybutenolide analogs of mexicanolide-type limonoids while erythrocarpine Q – V are phragmalin-type limonoids possessing a 1,29-oxymethylene bridge with either benzoyl or cinnamoyl moiety in their structures. Mosquito larvicidal activity revealed that crude DCM extract of C. erythrocarpus possessed a good larvicidal effect against Aedes aegypti larvae in 48 h (LC50 = 153.0 ppm). Subsequent larvicidal activity of isolated compounds indicated that erythrocarpine G (10) and 14-deoxyxyloccensin K (11) were responsible for the enhanced larvicidal effect of the extract, reporting LC50 values of 18.55 ppm and 41.16 ppm, respectively. Moreover, residual activity testing of the crude DCM extract revealed that the duration of its larvicidal effects is up to 14 days, where it maintained a 98 % larval mortality throughout the test period, under laboratory conditions.